MENGGALI POTENSI DESA LEWAT TRANSFORMASI DIGITAL BERBASIS KEARIFAN LOKAL DI DESA BATULAWANG, KECAMATAN CIPANAS - Nugraha, Mohamad Sigit Adi; Kartini, Iis; Chotimah, Destiana Husnul (JURNAL ABDIMAS PLJ, 2025)
The development of information and communication technology (ICT) has brought significant changes in various aspects of life, including in village governance. Digitalization is one of the main strategies in efforts to improve the quality of public services, administrative efficiency, and empower the economy of village communities. This community service activity aims to explore the potential of the village by implementing digitalization that can grow and develop the capabilities of UMKM into strong, independent and technology-literate businesses, boost the local economy and standard of living of the people in Batulawang Village, increase the role of UMKM so that the community knows that the place is the production site of the UMKM. The research results show that digitalization has increased the effeciency og village governance through digital information systems that accelerate administrative processes and public services.